Upravljanje vzdrževanja - Drstvenšek, Igor; Leber , Marjan (University of Maribor Press, 2020)
Maintenance Management. The textbook describes maintenance functions designed to determine performance and ensure the efficiency of the production process. To understand production efficiency, the concepts of efficiency, reliability and maintenance of production equipment and their impact on maintenance costs are first explained. Integrated productive maintenance is a concept that has succeeded in bringing together all the good practices that have evolved through the development of preventive maintenance, reliability based maintenance, integrated quality management (TQM) and the so-called lean manufacturing principles. Aspects of introducing integrated productive maintenance are presented, with an emphasis on methods that have proven successful in the Western world. The most important of these is the measurement of total efficiency, which shows the magnitude of production losses. The 5S, SMED, and 20 key methods described below serve to eliminate basic company losses and thereby increase the factor of total equipment efficiency.